2020
DOI: 10.1186/s12913-020-05731-3
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of HIV testing among adolescents and associated adolescent-friendly services

Abstract: Background HIV testing remains low among adolescents. Making public health services more adolescent-friendly is one strategy used to encourage testing. However, it remains unclear whether government-led initiatives have a meaningfully impact. Methods The current study is observational and utilizes two sources of data (health-facility and adolescent-level) from one round of data collection of an on-going, longitudinal impact evaluation of a pilot cash plus program targeting adolescents. This study linked data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Similar to our study findings, other studies have shown that AYP prefer to access services in community-based spaces compared to the health facility [33,34]. A systematic review of interventions to prevent unintended and repeat pregnancy among young people in low and middle-income countries found that out of seven interventions that had a positive impact on contraceptive use, five were community-based [20].…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our study findings, other studies have shown that AYP prefer to access services in community-based spaces compared to the health facility [33,34]. A systematic review of interventions to prevent unintended and repeat pregnancy among young people in low and middle-income countries found that out of seven interventions that had a positive impact on contraceptive use, five were community-based [20].…”
Section: Discussionsupporting
confidence: 89%
“…The AFHS was defined as an evidence-based and specialized approach to addressing health system barriers and catering to developmental needs by providing a more accessible, acceptable, equitable, appropriate, and effective social environment for young people [ 38 ]. A recently published systematic review study supported that AFHS in health facilities and clinical settings positively influenced health service utilization for HIV testing and other sexually transmitted diseases or performing preventive behaviors in Sub-Saharan Arica [ 39 ]. However, there is a lack of understanding and limited knowledge in the literature regarding implementing appropriate strategies for delivering AFHS to help young adolescents receive HIV testing in resource-constrained out-of-facility settings [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…3). For institutions within SSA, which accounted for 41.1% [44] of total author affiliations, South Africa singularly represented 38.6% [17] of these affiliations. The East African region represented 47.7% [21] affiliations, and West Africa and Central Africa represented 11.4% [5] and 2.3% [1], respectively.…”
Section: Lead Author Affiliationmentioning
confidence: 99%